Pengaruh Ukuran Perusahaan, Struktur Modal, Likuiditas dan Profitabilitas terhadap Nilai Perusahaan (Studi Pada Perusahaan Telekomunikasi yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2010-2017) - Afif Reyhan Fauzi; Rosyeni Rasyid (Universitas Negeri Padang, 2019)
This study aims to analyze the effect of Company Size, Capital Structure, Liquidity and Profitability on Firm Value. The type of research used in this study is comparative causal research. Causal comperative research is a research activity that seeks information about why a causal relationship occurs, and researchers try to trace the relationship back. Researchers take one or more consequences as devendent variables and test the data by tracing back to the past to look for causes, causes, interrelationships and their meanings. Company values tested in this study include Company Size, Capital Structure, Company Liquidity and Profitability. Hypothesis testing is done using multiple regression models with a sample of 34 observations from telecommunications companies listed on the Indonesia Stock Exchange during the period 2010-2017. The results of this study prove empirical evidence that: (1) Company Size does not affect Company Values, (2) Capital Structure does not affect Company Values, (3) Liquidity does not affect Company Values, (4) Profitability affects Company Values Keywords: Company Value Company Size, Capital Structure, Liquidity, Profitability